Crossing the boundaries: collaborations between mathematics and science departments in English secondary (high) schools. Issue 4 (1st October 2020) - Wong, Victoria; Dillon, Justin
ABSTRACT: Background : There are frequent calls in the literature for school science and mathematics departments to collaborate, largely in response to perceived overlaps between the two subjects in the context of Science, Technology, Engineering and Mathematics (STEM). Yet few studies explore how such collaborations might work. This paper is unusual both in its focus on mathematics/science collaborations which have not arisen from a specific short-term intervention and in its focus on the views of practising teachers rather than policy-makers or curriculum developers. Purpose : We ask how and why collaborations get started and explore how mathematics and science departments actually work together in secondary (high) schools in England. We ask what some of the affordances and challenges are in both initiating and sustaining collaborative practice. Design and methods : Six schools were identified and visited and semi-structured interviews carried out with the 15 teachers most closely involved in collaborating, to explore their perspectives and insights. Results : The findings show that collaborations are possible, though they are challenging to sustain, and they can be approached in a number of ways. Mathematics/science collaboration can be a key site of professional learning for teachers, particularly about the 'other' curriculum. Informal conversations across departments were highly valued but tended to be between those with a well-established pre-existing relationship. While physical structures can promote collaboration, it needs strong support from senior leadership teams to both begin and continue. Conclusion : Contrary to the commonly espoused view that there are many overlaps between mathematics and science in school, it can be a significant challenge for teachers to find them. Collaboration is neither straightforward to begin nor to sustain. Researchers and policy-makers should thus be cautious about recommending collaboration as straightforward for science and mathematics teachers to adopt. These conclusions provide a major challenge to simplistic advocacy of STEM in schools.